Personality affecting coaches-athletes relationship of Malaysian football teams / Abbylolita Sullah and Chee Hian Tan - Sullah, Abbylolita; Tan, Chee Hian (Faculty of Sports Science and Recreation, University Press of Universiti Teknologi MARA, 2020)
Personality has a great effect on performance and coach-athlete relationship in a team. Sportsscientist asserts that a lack of certain personality traits could help to explain “why some individualsgifted at sport do not thrive at elite level.” Therefore, the purpose of this study was to examine anydifferences of personality traits between coaches and players of Malaysian football teams as well toidentify any differences concerning to personality traits among Malaysian successful and lesssuccessful football teams. (n =16) coaches and (n = 200) players of the Malaysia Super League andMalaysia Premier League were identified to participate in the modified GEQ (2009) which measuredpersonal attributes and personal qualities. Independent t-test apply and the results indicated that thenull hypothesis was rejected with the statistically of n (214); t = 2.441, p = .015; <.05 and n (214); t=2.434, p = .020; <.05. Personal qualities and attributes showed significant high mean value forMalaysian successful football teams n (106); t = 4.947, p = .000; <.05. This study distinguishedpersonality traits that seem to set apart the successful high-performing coach and athletes. This studyhas contributed to Coaching Science, the body of knowledge.